2019
DOI: 10.1016/j.appet.2019.104404
|View full text |Cite
|
Sign up to set email alerts
|

Teammate influences and relationship quality are associated with eating and exercise psychopathology in athletes

Abstract: Teammates have a powerful influence on athletes' eating attitudes / behaviours, but less is known about the relative importance of teammate influence mechanisms. The primary aim of this study was to explore the relationships and predictive associations between teammate influences (e.g., modelling of teammates' disordered eating; supportive teammate friendships) and athletes' eating and exercise attitudes and behaviours. A further aim was to identify the presence of any gender differences. Athletes (N = 1172, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 70 publications
(80 reference statements)
1
16
1
Order By: Relevance
“…It could be that the effects are more subtle than we had anticipated, and as such, the sample was underpowered to detect them. Although body dissatisfaction and disordered eating are frequently observed in highly competitive athletes (e.g., collegiate, professional, elite) (Kerr-Gaffney et al, 2018;Palermo and Rancourt, 2019;Scott et al, 2019a), our sample was predominantly (64%) engaged in club and recreational levels of athletics. It may be that differences in eating disorder risk as a function of teammate interdependence are better observed in more competitive environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that the effects are more subtle than we had anticipated, and as such, the sample was underpowered to detect them. Although body dissatisfaction and disordered eating are frequently observed in highly competitive athletes (e.g., collegiate, professional, elite) (Kerr-Gaffney et al, 2018;Palermo and Rancourt, 2019;Scott et al, 2019a), our sample was predominantly (64%) engaged in club and recreational levels of athletics. It may be that differences in eating disorder risk as a function of teammate interdependence are better observed in more competitive environments.…”
Section: Discussionmentioning
confidence: 99%
“…Although published studies including male athletes are less common, men and boys may be at greater risk of disordered eating than women and girls when the type of sport, social environment of teams, assessment used, and specific disordered eating behaviors are examined ( Baum, 2006 ; Papathomas and Lavallee, 2012 ; Papathomas and Petrie, 2014 ; Pope et al, 2015 ; Chapman and Woodman, 2016 ; Joy et al, 2016 ; Rice et al, 2016 ). Moreover, the social environment and teammate interdependence (i.e., whether the competition is completed alone or as a team) can play a key role in physical and psychological outcomes of male and female athletes ( Evans et al, 2012 ; Martin et al, 2014 ), including in eating disorder risk ( Scott et al, 2019a , b ). Given the influence of peer groups in the risk of eating disorders ( Keel and Forney, 2013 ), team dynamics may be an important aspect of disordered eating risk that should be investigated further.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of teammate modelling of bulimic‐type eating behaviors was assessed using the BMS, adapted for athletes (Scott et al, ). The original scale (BMS; Stice, ) comprises five items that explore the extent to which teammates engage in self‐induced vomiting to control weight, binge eating, food restriction, preoccupation with weight/shape, extreme weight control behaviors and supplement use.…”
Section: Methodsmentioning
confidence: 99%
“…However, a link has recently been demonstrated between influences from sport relationships (e.g., coach and teammates) and athletes’ eating psychopathology (e.g., Shanmugam, Jowett, & Meyer, , ). Indeed, a recent systematic review (Scott, Haycraft, & Plateau, ) highlighted that an athlete's teammates can positively influence an athletes’ eating psychopathology (e.g., via supportive teammate friendships, Kipp & Weiss, ; Shanmugam et al, ). However, teammates may also negatively impact upon athletes eating psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies not only focused on sports injuries but also paid attention to the possible risks of nutrition, psychology, and environment that adolescent athletes may face. For example, the study of Charlotte [ 7 ] showed that teammates may have a positive or negative influence on eating and exercise attitudes/behaviors of athletes. This contributes to the development of team-based interventions to reduce or prevent adolescent athletes’ disordered eating and negative exercise attitudes/behaviors; however, the study lacked more longitudinal exploration, considering the role of moderating factors, such as sport type.…”
Section: Introductionmentioning
confidence: 99%